(untitled) (Third Sector Social Economic Review, 2025)
The main purpose of this article is to examine the effect of healthcare professionals’ motivation on their intrapreneurship. To achieve this goal, quantitative research methods were used. A survey form was sent via digital tools to employees determined by convenience sampling method from the population of healthcare professionals in Turkey, and the data obtained from 360 people were used for factor analysis, normality test, regression and correlation analyses. As a result of the factor analysis, employee motivation was grouped under three factors (extrinsic motivation, perceptual intrinsic and relational intrinsic motivation), and intrapreneurship was grouped under two factors (institutional and independent). According to the correlation analysis findings, it was determined that there was a moderate positive relationship between corporate intrapreneurship and all sub-dimensions of motivation, while independent intrapreneurship had a low positive relationship. As a result of the regression analysis, it was determined that motivation had a moderate, positive and significant effect on corporate intrapreneurship. It was also determined that motivation had a low, positive and significant effect on independent intrapreneurship. According to the results of the study, increasing the motivation of employees will positively affect their intrapreneurship. Improving the motivating factors (financial gain, suitable working environment, adequacy of healthcare equipment, facilities and materials, constructive behavior of managers, appreciation of management and staff, promotion and specialization opportunities) will also support intrapreneurship.